Statistical coherence of primary schooling in IPUMS-International integrated population samples for China, India, Vietnam and ten other Asia-Pacific countries. (September 2015) - McCaa, Robert; Cleveland, Lara; Kelly-Hall, Patricia; Ruggles, Steven; Sobek, Matthew
IPUMS-International disseminates harmonized census microdata for more than 80 countries at no cost, although access is restricted to bona-fide researchers and students who agree to the stringent conditions-of-use license. Currently over 270 samples are available, totaling more than 600 million person records. Each year, 15–20 additional samples are released, as more countries cooperate with the IPUMS initiative and the integration of 2010 round census samples is completed. With so much microdata so readily available, questions of data quality naturally arise. This article focusses on the concept of statistical coherence over time for a single concept, primary schooling completed. From an analysis of the percentage completing primary schooling by birth year for pairs of samples for 13 Asia-Pacific countries, outstanding coherence is found for four countries – China, Mongolia, Vietnam and Indonesia – with mean differences of less than 0.5 percentage points, regression coefficient ( b ) ranging from 0.93 to 1.07 and R 2 = 0.99. For the 13 countries as a group there is considerable variation overall with mean absolute difference as high as 16 percentage points, b ranging from 0.62–1.44 and R 2 = 0.65–0.99. As a whole, statistical coherence of primary schooling is outstanding. Nonetheless, to make expert use of the harmonized microdata, researchers are cautioned to carefully study the IPUMS integrated metadata as well as the original source documentation. National Statistical Offices not currently cooperating or that have not yet entrusted 2010 round census microdata are invited to do so.